Diabetes and poverty: A primer for resource poor countries - Shaikh, Altamash; Kumar, K. V. S Hari (Journal of Social Health and Diabetes, 2018)
Diabetes mellitus is assuming pandemic proportions and is affecting both the developed and developing countries. India and China are the two most populous countries in the world that account for one-sixth of the world population. The prevalence of diabetes is also very common in these two countries next to that of the United States of America. The unique characteristics of diabetes in Southeast Asians include low body weight, high visceral fat, and also the increased insulin resistance. The developing nations have to grapple with the dual burden of the nutrient deficiency and excess states. The resources allocated for the health are often scarce and have to be utilized optimally in these places. The course and complications of diabetes also differ between the developed and developing nations. In this review, we describe the unique characteristics of diabetes in poor countries and also suggest certain remedial measures to improve the same.
Keywords: Diabetes mellitus; India; poverty; socioeconomic status